Локальні поля напружень Чорногірського та Буркутського покривів Українських Карпат - Гайдук, Т. (Геологія і геохімія горючих копалин, 2009)
Розглянуто мезоструктурні парагенезиси Чорногірського, Буркутського та частково Свидовецького покривів у середній течії р. Чорна Тиса (Українські Карпати). Визначено морфологічні типи локальних полів напружень для фронтальної та щитової частин Буркутського та тилової частини Чорногірського покривів. Відзначено, що локальні поля напружень підпорядковані розломам другого та третього порядку, а вони - Чорнотисенському поперечному розривному порушенню. This paper contains information on reconstruction of the local fields of paleostress of the Chornahora (Black mtn.), Burkut and partly Svidovets nappes of the Ukrainian Carpathians. The territory of researches is in a difficult knot where above-mentioned nappes pull one to another. The reconstructions of the local fields of paleostress were conducted on the basis of study of cracks of the rocks. Principles of this method were developed by M. V. Gzovskiy and other known researchers. The local fields of tensions testify to the presence of bursting structures of transversal to reaching of the Ukrainian segment of Carpathian buildup. One of them there is the Chorna Tysa bursting structure which has the transversal to strike of Carpathians character inherited. About the presence of transversal structures of foundation in this territory wrote a lot of authors. This dislocation plays an important role in forming of structure of this territory. The local fields of tensions form a cracks band which submits dislocations with a break of continuity which are observed by geophysical methods, and partly in geological mapping. These faults in their turn submit Chorna Tysa dislocation with a break of continuity which after kinematic constructions is of a character of left-side displacement.